Synthesis and complexation of new unsymetrical 1,2-dihydroxyimino-3,6-diaza-7-phenylheptane - Sekerci, M (Inst Obs Neorg Khimii, 2000)
1-Amino-2-(N-benzylamino)ethane (1) has been obtained by the reaction of benzyl chloride and ethylenediamine. In a second step 1,2-dihydroxyimino-3,6-diaza-7-phenylheptane (2) has-been obtained by the reaction of (1) with anti-chloroglyoxime. The resulting 1,2-dihydroxyimino-3,6-diaza-7-phenylheptane ligand was reacted with transition metals such as Ni(II), Co(II) and Cu(II). The Cu(II) and Ni(II) complexes of these ligands are proposed to be squareplaner, while the Co(II) complexes are proposed to be octahedral with water molecules as axial ligands. The structures of the new materials were identified by using elemental analyses, infrared and H-1 NMR spectra, magnetic measurements, TGA and DTA techniques.
Keywords: Amine Oxime Ligands; Molecular-Structure; Metal Complexation; Crystal-Structures; Nickel(Ii); Cobalt(Ii); Palladium(Ii); Copper(Ii); (E,E)-Dioximes; Platinum(Ii)